Penelope Heynes' Full Stroke at 120 m of Her 200 m Breaststroke Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S. (1999)
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Penelope Heynes' full stroke at 120 m of her 200 m breaststroke gold medal race at the Atlanta Olympic Games 1996.